Diagnosis and Characterization of Ditylenchus destructor Isolated from Mazus japonicus in China - Wenwen Song; Mingming Dai; Qianqian Shi; Chen Liang; Fangmeng Duan; Honghai Zhao (Life, 2023)
The potato rot nematode (Ditylenchus destructor) is one of the most destructive pests in the production of tuber crops, resulting in severely decreased yields and inferior product quality. In 2021, a great number of nematodes were detected in the roots of Mazus japonicus, a weed that is harmful to crop growth, in Qingdao, Shandong Province, China. The present study was undertaken to characterize and identify the nematodes isolated from M. japonicus through morphological identification and molecular approaches. Their morphological characteristics were highly consistent with the descriptions of D. destructor Thorne, 1945. The nematodes collected from M. japonicus were identified as D. destructor haplotype B using D1/D2 and sequence characterized amplified region (SCAR) primers. PCR-ITS-RFLP analysis was conducted to monitor intraspecific variations. In addition, the phylogenetic analysis of the internal transcribed spacer (ITS) demonstrated that this D. destructor population was clustered in haplotype B, supported by a 100% bootstrap value. Another assay, in which M. japonicus was inoculated with a mixture of the life stages of D. destructor, was performed. This assay showed that M. japonicus exhibited a high susceptibility to D. destructor in pots. This is the first record of D. destructor parasitizing M. japonicus in China, and it is of great importance because M. japonicus could be a potential reservoir for D. destructor in the field.